2022
DOI: 10.4314/ajosi.v4i1.6
|View full text |Cite
|
Sign up to set email alerts
|

Dilemma of financial exclusion and inlusion in Africa: Can Nigeria, South Africa and Ghana be compared?

Abstract: This paper investigates the level of financial inclusion and exclusion in selected African countries with special attention to Nigeria, South Africa and Ghana in a comparative approach. The study utilized global survey data on financial inclusion index published by Global Findex. From the researcher‟s comparative analysis using the basic variables of financial inclusion, it was discovered that: in terms of financial service accessibility, bankable adult Nigerians have less access to financial services than Sou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…The availability dimension under the FI concept determines the capabilities of a company in terms of technology choice, market access and access to necessary resources that significantly contribute to the enhancement of the business. Nkwede [37] showed a significant association between financial availability and business performance, especially in developing countries. Availability of various financial services assists in performance, sales growth and productivity, according to a study by Harrison et al [38].…”
Section: Financial Inclusion Theories and Hypothesis Buildingmentioning
confidence: 98%
“…The availability dimension under the FI concept determines the capabilities of a company in terms of technology choice, market access and access to necessary resources that significantly contribute to the enhancement of the business. Nkwede [37] showed a significant association between financial availability and business performance, especially in developing countries. Availability of various financial services assists in performance, sales growth and productivity, according to a study by Harrison et al [38].…”
Section: Financial Inclusion Theories and Hypothesis Buildingmentioning
confidence: 98%
“…The study found a negative effect of financial inclusion and trade openness on economic growth in Zimbabwe. Nkwede (2015) examined whether financial inclusion promotes economic growth in Nigeria from 1981 to 2013. The study found that financial inclusion has a significant negative impact on economic growth in Nigeria.…”
Section: Theory and Empirical Reviewmentioning
confidence: 99%
“…By this, we mean that some of the models in the literature are very sensitive to small changes in model assumptions or sensitive to a change in one or more explanatory variables (e.g. Adeoye and Alenoghena, 2019; Nwafor, 2018; Nkwede, 2015, etc.). The nonrobustness of the models used in these papers is due to incorrect model specification.…”
Section: Areas For Future Researchmentioning
confidence: 99%
See 2 more Smart Citations